Sexually Transmitted Infections among Adolescents in Greater Letaba, South Africa: Prevalence and Gender-Specific Risk Factors - Leinett Thobakgale, Maite; Mpata Mokgatle, Mathildah; Kleinhans, Atholl; Hoque, Muhammad (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Adolescents remain highly vulnerable to sexually transmitted infections (STIs) due to behavioral, biological, and socio-cultural determinants, yet there is limited evidence from rural sub-Saharan Africa addressing the prevalence and gender-specific patterns of risk. This study aimed to determine the prevalence of STIs and associated risk factors among adolescents in the Greater Letaba sub-district of Limpopo Province, South Africa. A quantitative, descriptive, cross-sectional survey was conducted among 450 participants aged 18–24 years. Data on socio-demographics, sexual practices, STI-related symptoms, and health-seeking behaviors were collected and analyzed. The results showed that 44% of respondents reported STI-related symptoms within the past year, with genital discharge (44%) and dysuria (41%) being the most common. Male participants exhibited significantly higher engagement in risky sexual behaviors, including transactional sex, multiple or non-regular partners, and alcohol use during last intercourse (p<0.001). Males also demonstrated higher rates of condom use, negotiation confidence, and HIV testing uptake compared to females, who expressed greater willingness to test with a partner. The findings underscore the dual challenge of high-risk sexual practices and gendered disparities in STI prevention, suggesting the importance of targeted, gender-sensitive interventions. Integrating Islamic values of modesty, mutual responsibility, and protection of health can strengthen preventive strategies, aligning with the Sustainable Development Goals to improve adolescent and family health outcomes.